NOx and CO emissions and soot presence in partially premixed acoustically excited flames - Ferreira, D. S. [UNESP]; Lacava, P. T.; Ferreira, M. A.; de Carvalho, J. A. [UNESP] (Maney Publishing, 2009)
The pulsating combustion process has attracted interest in current research because its application in energy generation can offer several advantages, such as fuel economy, reduced pollutants formation, increased rate of convective heat transfer and reduced investment, when compared with other new techniques of combustion. An experimental study has been conducted with the objective of investigating the effects of combustion driven acoustic oscillations in the emission rates of combustion gases, especially carbon monoxide and nitrogen oxides, and soot presence in partial premixed flames in confined partially premixed liquefied petroleum gas flames. The results basically showed that a more uniform fuel/air mixture due to the presence of an acoustic field increases the NOx emissions in operations close to stoichiometric equivalence ratios and the frequency is the most important parameter. Carbon monoxide and soot reduced significantly.
Keywords: Pulsating combustion; Flames acoustically excited; Partial premixed flames